Osteochondral Lesions of the Talus: A Review on Talus Osteochondral Injuries, Including Osteochondritis Dissecans. (December 2021) - Bruns, Juergen; Habermann, Christian; Werner, Mathias
This is a review on talus osteochondritis dissecans and talus osteochondral lesions. A majority of the osteochondral lesions are associated with trauma while the cause of pure osteochondritis dissecans is still much discussed with a possible cause being repetitive microtraumas associated with vascular disturbances causing subchondral bone necrosis and disability. Symptomatic nondisplaced osteochondral lesions can often be treated conservatively in children and adolescents while such treatment is less successful in adults. Surgical treatment is indicated when there is an unstable cartilage fragment. There are a large number of different operative technique options with no number one technique to be recommended. Most techniques have been presented in level II to IV studies with a low number of patients with short follow ups and few randomized comparisons exist. The actual situation in treating osteochondral lesions in the ankle is presented and discussed.